THE INFLUENCE OF PERCEPTION OF CORPORATE SOCIAL RESPONSIBILITY, ORGANIZATIONAL CITIZENSHIP BEHAVIOR AND WORK ENVIRONMENT ON EMPLOYEE PERFORMANCE THROUGH TOTAL QUALITY MANAGEMENT AT PDAM TIRTA DHARMA LAMONGAN - Nur Adilah; Dewie Tri Wijayati Wardoyo; Andre Dwijanto Witjaksono (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
Employee performance is a crucial determinant of the success of public service organizations, including PDAM Tirta Dharma Lamongan, which is responsible for providing clean water services effectively, efficiently, and sustainably. This study aims to analyze the influence of Perception of Corporate Social Responsibility, Organizational Citizenship Behavior, and Work Environment on Employee Performance through Total Quality Management as a mediating variable. Using a quantitative approach, data were collected from PDAM Tirta Dharma Lamongan employees through a Likert-scale questionnaire and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results show that Perception of Corporate Social Responsibility, Organizational Citizenship Behavior, and Work Environment have a positive and significant effect on Employee Performance. Organizational Citizenship Behavior and Work Environment also have a positive and significant effect on Total Quality Management, while Perception of Corporate Social Responsibility does not significantly influence Total Quality Management. Furthermore, Total Quality Management has a positive and significant effect on Employee Performance. Mediation analysis reveals that Total Quality Management does not mediate the relationship between Perception of Corporate Social Responsibility and Employee Performance but successfully mediates the effects of Organizational Citizenship Behavior and Work Environment on Employee Performance. These findings indicate that proactive employee behavior and a supportive work environment contribute more effectively to performance improvement when integrated with a sustainable quality management system, highlighting the strategic role of Total Quality Management in enhancing employee performance within public service organizations.